A STUDY TO EXPLORE THE KNOWLEDGE, ATTITUDE, AND QUALITY OF LIFE AMONG CHRONIC RENAL FAILURE PATIENTS UNDERGOING HEMODIALYSIS AT PANIMALAR MEDICAL COLLEGE HOSPITAL AND RESEARCH INSTITUTE, CHENNAI. - Dr. Savithri K. B.; Mrs. Florence Nightingale K. A.; Mrs. Mudaliar Pushpa Kailash; Mrs. Pappu B.; Mr. Kavinpriyan.V.; Ms. Dhanalakshmi. M.; Ms. Dhanalakshmi.T.; Ms. Dhatchayini. D. (The Bioscan, 2026)
ackground: Chronic Kidney Disease (CKD) is a major global public health concern, with prevalence varying across regions. It is estimated that approximately 10–15% of the global adult population is affected by CKD. Evidence suggests that 30–60% of patients worldwide have inadequate knowledge regarding chronic renal failure (CRF), its progression, and the role of haemodialysis in disease management. Objectives: The objectives of the study were to assess the knowledge, attitude and quality of life of chronic renal failure patients undergoing haemodialysis. To Correlate knowledge, attitude and quality of life and to associate the level of knowledge, knowledge, attitude and quality of life with selected demographic variables chronic renal failure patients undergoing haemodialysis. Methods: An evaluative approach with a descriptive research design was adopted. A total of 134 patients undergoing haemodialysis were selected using a purposive non-probability sampling technique based on predefined inclusion criteria. Data on knowledge, attitude, and QoL were collected using a structured questionnaire and standardized tools. Statistical analysis was performed using descriptive and inferential statistics. Results: The findings revealed that the majority of participants 88 (65.67%) had inadequate knowledge, 35 (26.11%) had moderate knowledge, and only 11 (8.20%) demonstrated adequate knowledge regarding CRF and haemodialysis. Chi-square analysis demonstrated a highly significant association between knowledge level and age, education, marital status, and duration of dialysis (p < 0.0001), and a significant association with gender and employment status (p < 0.05). Attitude was significantly associated with age (p < 0.0001). QoL showed a significant association with marital status and duration of dialysis treatment (p < 0.0001). Conclusion: The study highlights that patients with chronic renal failure undergoing haemodialysis generally exhibit moderate levels of knowledge, attitude, and quality of life. Significant positive correlations were identified among knowledge, attitude, and QoL, with meaningful associations observed with selected demographic variables. The findings emphasize the importance of enhancing patient education and fostering positive attitudes, which may lead to improved quality of life and better health outcomes among patients undergoing haemodialysis.